Metabolic characteristics of skeletal muscle during detraining from competitive swimming - Costill, D.; Fink, W.; Hargreaves, M.; King, D.; Thomas, R.; Fielding, R. (Medicine & Science in Sports & Exercise, 1984)
After five months of intense training, eight male varsity swimmers were studied during four weeks of inactivity. Performance time did not change. The losses in trained parameters over that period were: - muscle glycogen decreased from 153 to 93 mM/kg; and - after a 200 yd swim at 90% of best time for the distance, blood lactate rose from 4.2 mM/l to 9.7 mM/l. After only one week, the oxidative potential of the swimmers' muscles and a greater disturbance in blood acid-base balance following a standard swim were observed. It was also contended that full conditioning may be lost completely within six to eight weeks following the cessation of training. Implications: In the weeks following cessation of swimming training the physiology changes as a result of decline in the muscles' respiratory capacity and a diminished oxygen transport system. The length of time that swimmers are given off from training, particularly after important championships, will determine the training state of the swimmers when they restart training. If trained effects are lost so quickly, it would seem that in the transition period between training seasons it would not be prudent to stop training, but rather to swim on a diminished schedule that would facilitate maintaining trained states or allow only small regressions. This is an important consideration because the time spent retraining is not time that will produce improvements over that achieved in the previous trained state. By allowing swimmers to detrain, coaches will restrict the potential of swimmers to improve.